What About Bob? - Marshall Anderson (Association of American Medical Colleges, 2007)
Abstract This resource is a biochemistry problem-based learning (PBL) case suitable for either first- or second-year medical students. It examines a patient who is diagnosed with chronic myelogenous leukemia. He is first treated with interferon alpha for a period of 14 months until the drug is no longer effective and other complications occur. He is then switched to Gleevec which has just been approved for use. This drug is very effective for this patient, but his oncologist informs the patient that Gleevec is not a cure and gives him information about bone marrow transplants. Students learn aspects of cell cycle, molecular biology, and oncogenes. Students in the first year of a medical school PBL curriculum have used this case to tackle the principles of cell cycle, chromosomal abnormalities, oncogene formation, and targeted chemotherapy.